The impact of abusive supervision by coaches on athlete burnout in Chinese culture - Li, Jingyan; Li, Xingyi; Sun, JunJun; Li, Jiangyuan; Li, Caixia; Fu, Yuantai; Yan, Changliang (Frontiers in Psychology, 2025)
BackgroundEmpirical research on abusive supervision by coaches within the Chinese cultural context remains notably limited. Grounded in self-determination theory, the present study aims to explore the underlying mechanisms through which coach abusive supervision contributes to athlete burnout among Chinese athletes.MethodsThis study employed a cross-sectional design and collected self-report questionnaire data from 301 athletes in China. A moderated mediation model was subsequently tested to examine the hypothesized relationships.ResultsThe findings indicate that the coach–athlete relationship mediates the association between abusive supervision and helping behavior. Moreover, a higher level of cognitive trust positively moderates the mediating effect of abusive supervision on the coach–athlete relationship, whereas the moderating role of affective trust is not statistically significant.ConclusionThe results indicate that as the level of coach abusive supervision increases, the quality of the coach–athlete relationship deteriorates, which in turn leads to heightened athlete burnout. Cognitive trust emerges as a significant moderating factor in this process. These findings suggest that fostering a supportive coach–athlete relationship—grounded in mutual respect and effective communication—remains a critical strategy for preventing athlete burnout.